Cardioneuroablation for reflex syncope or functional bradyarrhytmias: new insight from a single center experience - Valenti, Noemi; Di Monaco, Antonio; Romanazzi, Imma; Vitulano, Nicola; Troisi, Federica; Quadrini, Federico; Vitullo, Antonio; Sgarra, Luca; Caruso, Rosa; Anzelmo, Vincenzo; Guida, Pietro; Brunetti, Natale Daniele; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardioneuroablation (CNA) is a new approach to treat reflex syncope and functional bradyarrhytmias caused by autonomic imbalance. We report our experience using CNA.MethodFrom September 2022 to July 2023, we took care of 21 patients (mean age 42 ± 21 years; 62% male) affected by reflex syncope or functional bradyarrhythmias. All patients underwent CNA under conscious sedation targeting the superior and/or inferior paraseptal ganglionated plexus (GPs).ResultsNine patients were affected by vasovagal syncope (VVS) and twelve by functional bradyarrhythmias. In 3 cases (14%) the ablation was performed only on the GPs of the right atrium, while in the remaining 86% of cases we performed biatrial lesions. As regards the acute results, we highlighted an increase in sinus heart rate (12 ± 15 bpm, p = 0.001), a shortening of the PQ interval (−18 ± 18 msec, p < 0.001), a reduction of the correct sinus node recovery times (cSNRT) (−142 ± 204 msec, p = 0.114), a shortening of the AH interval (−31 ± 26 msec, p = 0.008), a reduction of the effective refractory period of the atrio-ventricular node (−156; interquartile range from −30 to −160 msec, p = 0.042) and an increase in the Wencheback point (27 ± 20 bpm, p < 0.001). At follow-up, a single patient, due to persistent symptoms and bradyarrhythmic disorder, underwent permanent pacemaker implantation; no other patient had recurrence of syncope, and all remained persistently asymptomatic.ConclusionOur results confirm the efficacy and safety of CNA for the treatment of VVS and functional bradyarrhythmias, although further studies are needed to support these findings.